Adrenal gland responses to lipopolysaccharide after stress and ethanol administration in male rats - Mohn, Claudia Ester (2011)
All forms of stress, including restraint stress (RS) and lipopolysaccharide (LPS) administration, activate the hypothalamic–pituitary–adrenal (HPA) axis. LPS binds to a recognition protein (CD14) and toll-like receptor 2/4 in different cells and tissues, including the adrenal gland, to induce the production of cytokines and cause upregulation of cyclooxygenase and nitric oxide synthase (NOS) enzymes. Acute ethanol exposure activates the HPA axis, but in some conditions prolonged administration can dampen this activation as well as decrease the inflammatory responses to LPS. Therefore, this study was designed to evaluate the adrenal response to a challenge dose of LPS (50 mg/kg) injected i.p., after submitting male rats to RS, twice a day (2 h each time) for 5 days and/or ethanol administration (3 g/kg) by gavage also for 5 days, twice daily. At the end of the experiment, plasma corticosterone concentrations and adrenal gland content of prostaglandin E (PGE) and NOS activity were measured as stress mediators. The results showed that repetitive ethanol administration attenuated the adrenal stress response to LPS challenge alone and after RS, by preventing the increase in plasma corticosterone concentrations and by decreasing the PGE content and NOS activity in the adrenal gland. Therefore, we conclude that moderate alcohol consumption could attenuate the effects of psychophysical stress and impair an inflammatory response.